Enhancing Marketing Performance: Leveraging Selling Orientation and Competitive Network Design for Optimizing Insurance Sales in the Halal Industry - Panjaitan, Roymon; Febrianur Ibnu Fitroh Sukono Putra; Elia Resha Fatmawati; Cahya, Handy Nur; Bobur Sobirov (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This study investigates the impact of selling orientation, sales training effectiveness, and design-network competition capability on enhancing marketing performance. A quantitative approach was utilised, employing a purposive sampling method to collect data from 274 insurance salespeople via a questionnaire survey conducted in major cities throughout Indonesia. Partial Least Squares Structural Equation Modelling (PLS-SEM) was utilised for data analysis to investigate causal relationships among the variables. This study enhances the existing literature on selling orientation and design-network competition capability by illustrating the significant mediating role of design-network competition capability within the framework of sales training and orientation. This research presents empirical evidence regarding the strategic significance of design-network competition capability in enhancing market adaptability and responsiveness. The findings indicate that managers ought to incorporate the development of design-network competition capability into their training and sales orientation strategies, especially in industries characterised by significant market dynamics.Penelitian ini menyelidiki pengaruh orientasi penjualan, efektivitas pelatihan penjualan, dan kemampuan kompetisi jaringan desain terhadap peningkatan kinerja pemasaran. Pendekatan kuantitatif digunakan dengan metode purposive sampling untuk mengumpulkan data dari 274 tenaga penjual asuransi melalui survei kuesioner yang dilakukan di kota-kota besar di Indonesia. Analisis data dilakukan menggunakan Partial Least Squares Structural Equation Modelling (PLS-SEM) untuk menguji hubungan kausal antar variabel. Penelitian ini memperkaya literatur yang ada mengenai orientasi penjualan dan kemampuan kompetisi jaringan desain dengan menunjukkan peran mediasi yang signifikan dari kemampuan kompetisi jaringan desain dalam kerangka pelatihan dan orientasi penjualan. Penelitian ini memberikan bukti empiris tentang pentingnya kemampuan kompetisi jaringan desain sebagai strategi untuk meningkatkan adaptabilitas dan responsivitas pasar. Temuan ini menyarankan bahwa manajer perlu mengintegrasikan pengembangan kemampuan kompetisi jaringan desain ke dalam strategi pelatihan dan orientasi penjualan mereka terutama pada industri yang ditandai dengan dinamika pasar yang tinggi.